Structural, syntactic, and statistical pattern recognition : joint IAPR International Workshop, S+SSPR 2016, Mérida, Mexico, November 29-December 2, 2016, Proceedings /: joint IAPR International Workshop, S+SSPR 2016, Mérida, Mexico, November 29-December 2, 2016, Proceedings. (2016) - Unknown
No abstract available